2011
DOI: 10.1051/0004-6361/201117190
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a massive X-ray luminous galaxy cluster atz = 1.579

Abstract: We report on the discovery of a very distant galaxy cluster serendipitously detected in the archive of the XMM-Newton mission, within the scope of the XMM-Newton Distant Cluster Project (XDCP). XMMUJ0044.0-2033 was detected at a high significance level (5σ) as a compact, but significantly extended source in the X-ray data, with a soft-band flux f (r < 40 ) = (1.5 ± 0.3) × 10 −14 erg s −1 cm 2 . Optical/NIR follow-up observations confirmed the presence of an overdensity of red galaxies matching the X-ray emissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 31 publications
7
101
0
Order By: Relevance
“…An additional multi-band analysis has revealed that the star formation activity in this cluster increases with the environment density, with star forming galaxies being mainly located at the center of the system (Tran et al 2010). A similar trend has been observed in three other X-ray selected galaxy clusters, two newly confirmed at z = 1.56 ) and z = 1.58 (Santos et al 2011) and one at z = 1.46 (Hilton et al , 2010. However, the galaxy red-sequence of these systems has not yet been fully established yet, indicating that the members are still building their stellar mass via star formation activity.…”
Section: Introductionsupporting
confidence: 76%
“…An additional multi-band analysis has revealed that the star formation activity in this cluster increases with the environment density, with star forming galaxies being mainly located at the center of the system (Tran et al 2010). A similar trend has been observed in three other X-ray selected galaxy clusters, two newly confirmed at z = 1.56 ) and z = 1.58 (Santos et al 2011) and one at z = 1.46 (Hilton et al , 2010. However, the galaxy red-sequence of these systems has not yet been fully established yet, indicating that the members are still building their stellar mass via star formation activity.…”
Section: Introductionsupporting
confidence: 76%
“…More generally, we note that the X-ray emission of all four z > 1.5 known clusters appears to be significantly affected by point sources (there is no Chandra image published yet for Santos et al 2011;Fassbender et al 2011, but the XMM images look very compact). Furthermore, clusters like IRC-0218A will certainly always escape direct X-ray detection in the XMM or Chandra archive for techniques solely based on the search for extended X-ray emission.…”
Section: Discussionmentioning
confidence: 75%
“…Two of them have been primarily detected in the X-ray waveband Santos et al 2011). The other two were identified through an overdensity of red galaxies; weak X-ray emission was found a posteriori to be associated with both of them (Papovich et al 2010;Gobat et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Also, they will provide a key to understanding the origin of the environmental dependence of galaxy properties observed at low redshifts (e.g., Lewis et al 2002;Gómez et al 2003;Tanaka et al 2004). Dedicated effort has identified a number of high-redshift groups and clusters of galaxies at z 1.5 (e.g., Kurk et al 2009;Tanaka et al 2010aTanaka et al , 2013Fassbender et al 2011;Gobat et al 2011;Nastasi et al 2011;Santos et al 2011;Spitler et al 2012;Stanford et al 2012;Muzzin et al 2013). Among them, a z = 1.61 group, which is likely a progenitor of a present-day massive cluster, is carefully studied by Tanaka et al (2013) and they showed that the group already exhibits a prominent red sequence of quiescent early-type galaxies formed at z f = 3 (single stellar population equivalent).…”
Section: Introductionmentioning
confidence: 99%